Subspecies Range of Little Known North Sumatran Prevost's Squirrel Callosciurus prevostii piceus (Rodentia: Sciuridae) - Nur Rachman; Ali, Muhammad Sayidina; Tamam, Asep Badru; Wahyudi, Tedi; Effendi, Surianto; Aritonang, Sahat; Iqbal, Muhammad (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
North Sumatran Prevost's Squirrel Callosciurus prevostii piceus (Peters, 1866) is an endemic subspecies of terrestrial squirrel that only found in northern Sumatra, Indonesia. On 11 December 2022, we observed and documented C. prevostii piceus in Mugo Rayeuk Village (04°25'N, 96°10'E), Panton Reu Subdistrict, Aceh Barat District, Aceh Province, Sumatra. To review subspecies range, we compile published and unpublished records of C. prevostii piceus. Our study suggests C. prevostii piceus range from Aceh Barat of Aceh Province to Labuhan Batu of North Sumatra Province.